Rancang Bangun Aplikasi Tes Toefl Online Berbasis Web dengan Penilaian Otomatis pada Lembaga Bahasa Asc Indonesia - Wandi Aprianto (LPPM Universitas Mulia, 2025)
English proficiency is a crucial aspect in both academic and professional fields. The Test of English as a Foreign Language (TOEFL) is widely used as a standard to measure an individual's English language competency. However, conventional TOEFL testing methods still face limitations, such as delays in scoring and complex administrative processes. Therefore, this study aims to design and develop a web-based online TOEFL test application with an automated scoring system at the ASC Indonesia Language Institute. The development of this application follows the waterfall method, which includes analysis, design, implementation, and maintenance phases. The application is built using the Laravel framework for the backend, Vue.js for the frontend, and MySQL as the database for data storage. The automated scoring system is implemented using a rule-based scoring algorithm aligned with TOEFL standards. Testing results indicate that the developed application provides an efficient testing experience with fast and accurate scoring processes. Additionally, the test result reporting feature allows participants and administrators to analyze English language proficiency in more depth. In conclusion, this application offers an innovative solution for language institutions to enhance the effectiveness and efficiency of digital TOEFL test implementation.